Bank Transparency and Loan Loss Provisioning Behaviour: A Study of Islamic Banks in Different Countries - Oyekanmi, Adedoyin (2013)
The objective of this research is to determine if Islamic banks use loan loss provisioning for discretionary or non-discretionary purposes. Considerable attention has been drawn towards the loan loss provisioning practices of managers and how transparent the banking industry actually is. The Islamic banking industry represents a sector of the banking industry which is very dynamic and unique since it is based on the teachings of the Quran and Islamic laws (Shari’ah). A sample of 23 Islamic banks from 12 diverse countries was used to examine the use of loan loss provisions for capital management and income smoothing purposes by Islamic banks over the period 2006-2012. Investigations were also specifically conducted to determine their provisioning practice during the 2007-2009 global financial crisis.